Myrmicine ants of Nepal with six new records and updated species list (Hymenoptera: Formicidae: Myrmicinae) - Subedi, Indra Prasad; Budha, Prem Bahadur; Yusupov, Zalimkhan M.; Bharti, Himender (Nepalese Journal of Zoology, 2022)
Six ant species from the subfamily Myrmicinae are recorded as new to Nepal, namely Myrmica rhytida Radchenko & Elmes, 1999, Myrmicaria brunnea Saunders, 1842, Pheidole nodus Smith 1874, Strumigenys godeffroyi Mayr, 1866, S. virgila Bolton, 2000, and Temnothorax wroughtonii (Forel, 1904). The type locality, examined materials, worker diagnosis, and global distribution of each newly recorded species are provided, along with images of habitus in profile and head in full-face views. The list of 69 species of Myrmicine ants is provided with their province-specific distribution in Nepal.